Implementasi Algoritma Fuzzy C-Means dalam Mengelompokkan Kecamatan di Tana Luwu Berdasarkan Produktifitas Hasil Perkebunan - Bobby Poerwanto; Baso Ali (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
This study aims to classify sub-districts in Tana Luwu (Kabupaten Luwu, Luwu Timur, Luwu Utara, dan Palopo City ) using Fuzzy C-Means algorithm. The data used are data from BPS on the results of estate crops, namely coconut, oil palm, coffee, pepper, cocoa, clove, and land area. The results obtained from this study are from 45 sub-districts, there are 8 districts that are included into productive categories namely Burau, Sabbang, Mappedeceg, Baebunta, West Malangke, Sukamaju, Bone-Bone, and Tanalili. In addition, this study also found that matrix pseudo-partition selection can affect this algorithm in terms of the number of iterations produced.